Trascendental meditation effects in the sports performance in high performance athletes. - López Trejo, V.; Murguia, G.; Villalobos, S.; De Santiago, M.; Fritzler, W. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: TM Transcendental meditation is a technique of Indian origin, who has amply demonstrated its health benefits, as it has been used successfully in preventing cardiovascular diseases and those resulting from stress. There is little evidence of its usefulness in the sport even though it has been applied to high performance athletes. This research aims to establish the effectiveness of Transcendental Meditation TM to evaluate a series of physiological, anthropometric, psychological, biochemical and physical in elite athletes of the Football University and Sports Science (UFD acaronym in spanish). Methods: This experimental research was using the TM technique in a group of players, high-performance, compared with a control group of similar characteristics training and competition, selected at random. The experimental group (EG) received an induction course to the art and technique practiced 2 times daily for 4 months, were measured for biochemical variables, psychological, electroencephalographic, physical, physiological and anthropometric at the beginning and end of study both groups. Results: A sample of student athletes of the Alto Rendimiento Tuzo including 15 athletes in the EG and 15 in the GC, the average age in both groups was 16.6 years and shared similar demographic characteristics. The most significant quantitative result was the reduction of anxiety in the GE as demonstrated statistical significance compared with the control group and between the first and second evaluation of group P = 0.0000041, the other variables showed no significant differences. With regard to qualitative variables 75% of students reported an overall improvement after meditating and 45% reported improvement in sport performance, which was not confirmed quantitatively. Discussion: This study demonstrated that TM does not improve athletic performance, and anthropometric variables, although it reduces stress and anxiety in athletes. Among the evaluated biochemical variables creatine phosphokinase is found that it decreased significantly in the experimental group which was reflected in the reduction of sports injuries. This can be an effective tool to improve pre-competitive conditions and if it becomes a daily practice, perhaps could contribute to the improvement of sports variables secondarily.